Peran Self-Efficacy dalam Mengatasi Academic Burnout pada Siswa SD Fullday - Indaka, Rezqika Allaya; Utami, Adnani Budi; Haque, Sayidah Aulia'ul (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to determine the relationship between self efficacy and academic burnout in fullday school elementary school students in Gresik. This study uses a correlational quantitative method using a sampling technique, namely cluster random sampling. The population of this study were all fullday school elementary school students in Gresik and the sample used was 384 students who were represented from grades 4, 5, and 6. Hypothesis test analysis using product moment correlation. The results of this study showed a correlation coefficient (rxy) of - 0.431 with a significance of 0.000 (p,0.001), indicating that there is a very significant relationship between self efficacy and academic burnout in fullday school students in Gresik. This indicates that the higher the self-efficacy possessed, the lower the academic burnout experienced, on the contrary, the lower the self-efficacy possessed, the higher the academic burnout experienced.